Eficiência em mercados acionários sob a percepção de variáveis econômicas diversas - Albuquerque, Gleidson de França (2010)
This paper investigates the efficient market hypothesis, which indicates a situation where investors are not able to develop a familiarity with past patterns of returns in order to obtain extra profits. It is used a sample containing 25 markets over the period January 1990 to January 2010. Econometric Methodology consists in exploiting five unit root tests, between which Pesaran, Smith e Yamagata (2009) is in relief, which assumes that there exists a number of variables that are simultaneously affected by a given set of unobserved common factors. Main results reject the efficient market hypothesis, indicating possibilities of exploiting inefficiency for obtaining extra profits.